PENERAPAN WEIGHTED PRODUCT UNTUK MENENTUKAN MUSYRIF-MUSYRIFAH MA’HAD SUNAN AMPEL AL-ALY UIN MAULANA MALIK IBRAHIM MALANG - Hardiana Riski RIswanto; Rofi'ul Khasanah; Layla Qomariyah; Siti Kholifah (Department of Science and Technology Ibrahimy University, 2020)
Decision support systems mushrifs / ah which is currently still based only add data themselves and upload files online requirements. Although candidates mushrifs / ah will pass some other selection processes, the recommendations of the top leaders become more value every candidate mushrifs / ah listed. So that the electoral system is still subjective. This research aims to develop a decision support system mushrifs / ah to implement the Decision Support System (DSS) that mushrifs decision support systems can be more objective. There are several criteria that the reference of the decision support system mushrifs / ah. One method used to resolve the existing problems in some of these criteria is a method of WP (Weighted Product). This method of evaluating several alternatives to atribuat or a set of criteria, where each attribute each independently of one another. By applying the WP method combined with the concept of DSSD then the resulting value of Confusion matrix (recall, percision, f-measure and accuracy) is obtained by finding the value of a comparison between the test data with the data pattern. And the confusion matrix obtained value that gets results Accuracy 75.00%, 71.43% recall, precission 83.33% and 76.92% F-Measure.